IFLA Library Reference Model (IFLA LRM), pomemben korak k sodobnim bibliografskim informacijskim sistemom - Žumer, Maja (Knjižnica, 2017)
IFLA LRM model, the result of the harmonisation of FRBR family of models, is presented. LRM is a high-level abstract model and serves primarily as a framework for the development of consistent extensions. The entity-relationship formalism, the same as in the FRBR family, was chosen for the definition of the model. User tasks as the basis of the model are presented first, followed by the entities and examples of attributes and relationships. Aggregates are specifically addressed, since they often present a modelling problem.
Keywords: FRBR Family; IFLA LRM; conceptual models; FRBR; information systems; konceptualni modeli; informacijski sistemi